Transcription start site analysis reveals widespread divergent transcription in D. melanogaster and core promoter-encoded enhancer activities. Issue 11 (6th April 2018) - Rennie, Sarah; Dalby, Maria; Lloret-Llinares, Marta; Bakoulis, Stylianos; Dalager Vaagensø, Christian; Heick Jensen, Torben; Andersson, Robin
Abstract: Mammalian gene promoters and enhancers share many properties. They are composed of a unified promoter architecture of divergent transcripton initiation and gene promoters may exhibit enhancer function. However, it is currently unclear how expression strength of a regulatory element relates to its enhancer strength and if the unifying architecture is conserved across Metazoa. Here we investigate the transcription initiation landscape and its associated RNA decay in Drosophila melanogaster . We find that the majority of active gene-distal enhancers and a considerable fraction of gene promoters are divergently transcribed. We observe quantitative relationships between enhancer potential, expression level and core promoter strength, providing an explanation for indirectly related histone modifications that are reflecting expression levels. Lowly abundant unstable RNAs initiated from weak core promoters are key characteristics of gene-distal developmental enhancers, while the housekeeping enhancer strengths of gene promoters reflect their expression strengths. The seemingly separable layer of regulation by gene promoters with housekeeping enhancer potential is also indicated by chromatin interaction data. Our results suggest a unified promoter architecture of many D. melanogaster regulatory elements, that is universal across Metazoa, whose regulatory functions seem to be related to their core promoter elements.